Top-down motif discovery in biological sequence datasets by genetic algorithm - Baloglu, Ulas Baran; Kaya, Mehmet (Ieee Computer Soc, 2006)
This paper presents a novel approach for motif discovery. Finding motif in biosequences is the most important primitive operation in computational biology. There are many computational requirements for a motif discovery algorithm such as computer memory space requirement and computational complexity. To overcome the complexity of motif discovery, we propose an alternative solution integrating genetic algorithm and top-down data mining, approaches for eliminating multiple sequence alignment process. The experimental results. demonstrate that the proposed method outperforms two well-known motif discovery algorithms, called MEME and Gibbs Sampler.
1st International Conference on Hybrid Information Technology -- NOV 09-11, 2006 -- Cheju Isl, SOUTH KOREA
Keywords: Alignment; Dna